Cost-effectiveness analysis of nivolumab plus ipilimumab plus two cycles of platinum-doublet chemotherapy versus platinum-doublet chemotherapy alone for first-line treatment of stage IV or recurrent non-small cell lung cancer in the United States. (31st December 2022) - Polyzoi, Maria; Sandhu, Hera; Maervoet, Johan; Yuan, Yong; Chaudhary, Mohammad A.; Varol, Nebibe; Lee, Adam; Dale, Peter; Jones, Cheryl; Lubinga, Solomon J.; Penrod, John R.
Abstract: Aim: This economic analysis evaluated the cost-effectiveness of nivolumab (NIVO) plus ipilimumab (IPI) plus two cycles of platinum-doublet chemotherapy (PDC) compared with four cycles of PDC as first-line treatment for patients with advanced NSCLC in the United States (US). Methods: A partitioned survival model was constructed with three mutually exclusive health states: progression free, progressed disease, and death. The analysis was conducted from a US healthcare payer perspective, using a time horizon of 25 years. Costs and outcomes were discounted at 3% annually. Survival outcomes from CheckMate 9LA were extrapolated with longer follow-up data from CheckMate 227 Part 1 (NIVO + IPI) and validated against data from other relevant clinical trials and real-world registries. Health-related quality of life utility values were derived from EQ-5D-3L data collected in CheckMate 9LA. US-specific costs (2020 dollars) were used for disease management; drug acquisition, administration, and monitoring; end-of-life care; adverse events; and subsequent treatments. Model outcomes included life years (LYs) gained, quality-adjusted LYs (QALYs) gained, and incremental cost-effectiveness ratio (ICER) for NIVO + IPI + PDC versus PDC. Sensitivity and scenario analyses were conducted. Results: NIVO + IPI + PDC was associated with higher projected health benefits than PDC, including gains in LYs (3.71 vs 1.89) and QALYs (2.86 vs 1.37), and higher costs ($317, 581 vs $119, 909). The ICER was $132, 960/QALY gained. NIVO + IPI + PDC had a 78–100% probability of being cost-effective at a willingness-to-pay threshold of $150, 000–$250, 000/QALY. Sensitivity and scenario analyses indicated that the results were robust to changes in key parameters. Limitations: The inherent limitation in extrapolating clinical trial data was mitigated using data from the more mature CheckMate 227 Part 1 trial and validating the outcomes against data from other relevant trials and real-world registries. Conclusion: NIVO + IPI + PDC (two cycles) provides a new first-line treatment option for patients with advanced NSCLC that is cost-effective within a range considered acceptable in the US.